2019
DOI: 10.21873/invivo.11745
|View full text |Cite
|
Sign up to set email alerts
|

Hypermethylation of Corticotropin Releasing Hormone Receptor-2 Gene in Ulcerative Colitis Associated Colorectal Cancer

Abstract: Background/Aim: The difficulty of early diagnosis of colitis associated colorectal cancer (CACRC) due to colonic mucosal changes in long-standing ulcerative colitis (UC) patients is often experienced in daily clinical practice. Noninvasive objective monitoring for cancer development is advantageous for optimizing treatment strategies in UC patients. We aimed to examine the epigenetic alterations occurring in CACRC, focusing on DNA hypermethylation of CpG islands. Materials and Methods: The level of DNA methyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 48 publications
(59 reference statements)
1
9
0
Order By: Relevance
“…In silico analysis of CRFR2 methylation status revealed that all the emerged DMCs identified in transcription-related regions were hypermethylated in the CRC tissues compared to the healthy ones. This is in line with recent findings indicating positive correlation of hypermethylated CRFR2 (studied by an Infinium Human Methylation 450K array) with colitis-induced CRC [ 35 ]. Accordingly, the previously reported observations on diminished CRFR2 mRNA and protein expression in CRC cell lines and tissues [ 30 ] may be attributed to CRFR2 hypermethylation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In silico analysis of CRFR2 methylation status revealed that all the emerged DMCs identified in transcription-related regions were hypermethylated in the CRC tissues compared to the healthy ones. This is in line with recent findings indicating positive correlation of hypermethylated CRFR2 (studied by an Infinium Human Methylation 450K array) with colitis-induced CRC [ 35 ]. Accordingly, the previously reported observations on diminished CRFR2 mRNA and protein expression in CRC cell lines and tissues [ 30 ] may be attributed to CRFR2 hypermethylation.…”
Section: Discussionsupporting
confidence: 92%
“…We recently reported on an association of CRFR1 hypermethylation with the presence of steroid hormone receptors in breast cancer [ 34 ]. In addition, using genome-wide methylation approaches, Kobayashi et al found that hypermethylation of CRFR2 is correlated with colitis-induced CRC [ 35 ]. This is in line with our previous reports indicating that diminished or lost CRFR2 expression in CRC promotes tumor development and aggressiveness, including tumor immunoescape, by regulating molecular circuits involved in sustaining inflammation in the gut [ 30 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…UCN2/CRHR2 signal transduction can hinder the metastatic ability of colon cancer cells and negatively regulate the growth of colon cancer [38], However, the combination of UCN3 and CRHR2 can activate the Src/ERK/FAK pathway, which can promote the migration and invasion of colorectal cancer [39]. Angiogenesis is the basis of tumor occurrence and development, vascular endothelial growth factor VEGF is an effective inducer of angiogenesis.…”
Section: The Relationship Between Crh and Various Tumorsmentioning
confidence: 99%
“…Furthermore, regarding the CRHR2 gene, a recent study indicates higher levels of hypermethylation of the gene in patients with z colitis-associated CRC versus non-tumorous mucosa, which could be used in screening, prognostics, as well as evaluation of therapy outcomes in patients with UC-associated CRC [267]. These studies could also determine that hypermethylation of CRHR2 may be responsible (similarly as in the case of SM) for lowered tissue expression of this protein [96], but also cell spreading, being a high metastasis risk factor in CRC [98].…”
Section: Genetic and Epigenetic Changes Of Selected Nps And Crc Liver Metastasismentioning
confidence: 99%